2012
DOI: 10.1016/j.apenergy.2011.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the concept of compressed air energy storage (CAES) in lined rock caverns at shallow depth: A modeling study of air tightness and energy balance

Abstract: This paper presents a numerical modeling study of coupled thermodynamic, multiphase fluid flow and heat transport associated with underground compressed air energy storage (CAES) in lined rock caverns. Specifically, we explored the concept of using concrete lined caverns at a relatively shallow depth for which constructing and operational costs may be reduced if air tightness and stability can be assured. Our analysis showed that the key parameter to assure long-term air tightness in such a system was the perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(58 citation statements)
references
References 23 publications
0
52
1
5
Order By: Relevance
“…As indicated in Table 3, the permeability of the concrete lining was 7.0 × 10 -20 m 2 , while the permeability of the host rock and EDZ was estimated 1.5 × 10 -19 and 2.5 × 10 -17 m 2 , respectively. Kim et al (2012) showed that a concrete permeability as low as 1.0 × 10 -20 m 2 was sufficient to keep air leakage insignificant, regardless of the permeability of the EDZ and surrounding rock mass. We therefore focus our investigation on the tangential stress evolution in the concrete lining, which could potentially lead to fracturing and thus more significant leakage.…”
Section: Analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As indicated in Table 3, the permeability of the concrete lining was 7.0 × 10 -20 m 2 , while the permeability of the host rock and EDZ was estimated 1.5 × 10 -19 and 2.5 × 10 -17 m 2 , respectively. Kim et al (2012) showed that a concrete permeability as low as 1.0 × 10 -20 m 2 was sufficient to keep air leakage insignificant, regardless of the permeability of the EDZ and surrounding rock mass. We therefore focus our investigation on the tangential stress evolution in the concrete lining, which could potentially lead to fracturing and thus more significant leakage.…”
Section: Analysis Resultsmentioning
confidence: 99%
“…Model geometry and grid were similar to that used in Kim et al (2012) and Rutqvist et al, (2012), except for EDZ thickness and properties, which have since been updated based on investigation at the pilot test cavern ( Figure 9). It is a 2D model domain, corresponding to a 1 m thick vertical cross-section through the storage cavern, with a radius of 2.5 m, and with thicknesses for the concrete lining and EDZ of 0.5 and 0.6 m, respectively.…”
Section: Analysis Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salgi et al [19] analyzed the energy-balance effects of adding CAES to an energy-system. Kim et al [20] conducted a numerical modeling study of coupled thermodynamic, multiphase fluid flow and heat transport associated with CAES. The estimated GHG emission rate of a CAES plant combined with wind power is one-fourth that of cycle plants combined with natural gas (NG) and approximately one-tenth of that of pulverized coal plants [21].…”
Section: Introductionmentioning
confidence: 99%